Patient reported disability of ankle, hindfoot, midfoot and hallux metatarsophalangeal arthritis. Issue 3 (11th September 2017) - Christian, Matthew; Jeng, Clifford; Cerrato, Rebecca; Campbell, John T.; Koenig, Scott; O'Hara, Nathan; Hull, Michael
Category: Ankle, Ankle Arthritis, Hindfoot, Midfoot/Forefoot Introduction/Purpose: There has been in increased interest in foot and ankle arthritis in the literature in recent years. A significant focus of the literature has been which operative techniques are best for managing these problems. Some work has been done analogizing disability due to ankle arthritis to more familiar joints such as the hip. There is little data explaining how much patient reported disability is associated with each type of isolated foot and ankle arthritis. Various clinical rating scales have proven how debilitating foot and ankle arthritides can be to patients. The purpose of our study was to use Functional Foot Index (FFI) and Short Form-12 (SF-12) rating scales to compare the patient reported disability associated with ankle, hindfoot, midfoot, and hallux metatarsalphalangeal (MTP) arthritides. Methods: We retrospectively reviewed the FFI and SF-12 (both Physical Component Scores (PCS) and Mental Component Scores (MCS)) of patients who presented to a high volume orthopaedic foot and ankle practice between 2010 and 2016 with either ankle, hindfoot, midfoot or hallux MTP arthritis. We included patients between 18-65 years of age who underwent a surgical procedure for arthritis within 6 months of their initial presentation. We excluded patients with any medical or surgical co-morbidities known to affect disability scores. A total of 214 FFI and 195 SF-12 data sets were included. Results: Study population SF-12 PCS scores for all patients with ankle or foot arthritis were significantly lower than US age-based norms. Patients with ankle arthritis had the highest disability (FFI score 46.5, SF-12 PCS 32.3). Patients with midfoot and hindfoot arthritis had intermediate disability (Midfoot FFI score 34.9, SF-12 PCS 34.5; Hindfoot FFI score 44.3, SF-12 PCS 34.5). Patients with hallux MTP arthritis had the lowest disability (FFI score 32.9, SF-12 PCS 40.7). All FFI and SF-12 PCS scores were statistically significant. SF 12 MCS were not statistically significant. Conclusion: All patients with foot and ankle arthritis had increased disability compared to US age-based norms. Patients with ankle arthritis experience the most self-reported disability and patients with hallux MTP arthritis experience the least self- reported disability of the isolated types of arthritis in orthopaedic foot and ankle.